The Paradoxes of Neoantigenes in Predicting Better Prognosis of Cancer Patients - Rui-An Wang; Qing-Guo Yan; Jian-Guo Shi (Global Journal of Cancer Therapy - Peertechz Publications, 2016)
Increased neo antigens of cancer generated by mutations are reported to be associated with favorable prognosis of cancer patients. The interesting findings contradict the notions that cancers were caused by accumulation of gene mutations. The explanation of more efficient immuno surveillance provoked by the neo antigens contributes to the better outcomes also contradicts many more facts, i.e., the immuno surveillance in nature is inflammation which is a term of pathologist. The cancer related inflammation is widely accepted as a cancer promoting fact; more efficient immuno surveillance would result in more apoptosis of cancer cells. However, increased apoptosis were known to be associated with worse prognosis. Moreover, increasing evidence has shown that the expression of immune suppressing genes such as PD-1, PD-L1 and CTLA-4 were associated with better prognosis of cancer patients.